Analysis Of Residential Environmental Health Factors And The Incidence Of Tuberculosis: A Cross-Sectional Study - Eka Joni Yansyah; Fera Novitry (International Journal of Health Engineering and Technology, 2026)
Pulmonary tuberculosis remains a major public health problem, particularly in areas where residential environmental conditions do not meet healthy housing standards. Poor ventilation, inadequate natural lighting, unsuitable humidity, overcrowding, and inappropriate room temperature may increase the risk of domestic tuberculosis transmission. This study aimed to analyze the relationship between residential environmental health factors and the incidence of pulmonary tuberculosis in Batu Belang Jaya Village, the working area of Muaradua Public Health Center, South Ogan Komering Ulu Regency. This study used an analytical quantitative design with a cross-sectional approach. The study population consisted of 1,002 heads of households, and 286 respondents were selected using simple random sampling. Data were collected through interviews, observation, and direct measurement of residential environmental conditions. House ventilation was measured using a measuring tape, natural lighting was measured using a digital lux meter, and air humidity and room temperature were measured using a digital thermo-hygrometer. Data were analyzed using the Chi-square test with a significance level of 0.05. The results showed that 84 respondents (29.4%) were identified as pulmonary tuberculosis cases. The Chi-square test showed significant relationships between pulmonary tuberculosis incidence and house ventilation (p = 0.015), natural lighting (p = 0.038), air humidity (p = 0.014), occupancy density (p = 0.012), and room temperature (p = 0.046). Residential environmental health factors were significantly associated with pulmonary tuberculosis incidence. Environmental surveillance and healthy housing interventions should be strengthened to reduce household transmission risk.